TEST AUTOMATION IN HEALTHCARE SYSTEMS: ENSURING DATA INTEGRITY AND COMPLIANCE - Sandeep Akinepalli, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article explores the critical role of test automation in healthcare systems, focusing on its importance in maintaining data integrity and regulatory compliance. As healthcare undergoes digital transformation with the proliferation of electronic health records, telemedicine, and interconnected medical devices, the complexity of managing patient data has increased exponentially. The article discusses the challenges faced in implementing test automation, including sensitive data management, system integration, and regulatory adaptation. It also highlights the significant benefits of automated testing, such as improved efficiency, error reduction, and cost savings in regulatory compliance. Through an examination of current trends and case studies, the article provides a comprehensive overview of how test automation is shaping the future of healthcare technology and contributing to improved patient outcomes.